Efektivitas Pendekatan Etnomatematika pada Materi Sifat-Sifat Bangun Datar untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV di SDN Jagir I Surabaya - Asyita Al-Mufidah; Sri Hartatik; Nafiah; Kasiyun, Suharmono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the ethnomathematics approach to flat shape properties in improving the critical thinking skills of fourth-grade students. The research method used is quantitative with a One Group Pretest-Posttest Design. The data collection technique used in this study is a critical thinking skills test with the instrument used being a critical thinking skills test sheet. Data analysis in this study utilized the N-Gain test, assisted by Microsoft Excel to process the obtained data. Based on the critical thinking ability test calculated using the N-Gain formula, the overall average N-Gain was 0.7673, with an N-Gain score of 76.7%. This indicates that students' critical thinking abilities are in the high category, as they fall within the range of G >70. Based on the results of this study, the ethnomathematics approach is effective in improving critical thinking skills in fourth-grade mathematics learning. This study recommends that the ethnomathematics approach be considered more broadly as an innovative strategy in mathematics learning to improve students' critical thinking skills. It is important for teachers to integrate local cultural contexts into teaching materials, creating more relevant and meaningful learning experiences for students. It is hoped that students will become more active in understanding mathematical concepts through their own cultural lens. For future research, it is recommended to expand the scope of the study by exploring variations in ethnomathematics contexts and applying them to different educational levels and materials.